Utilizing WhatsApp Application in English Language Learning Classroom - Cicih Nuraeni; Lia Nurmalia (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2020)
WhatsApp (WA) is one of the most popular messaging applications which can be accessed by using mobile phone and Personal Computer (PC). Nowadays, most people prefer to use this application for communicating with other. In education field, WhatsApp also give beneficial features such as text, call, send video, audio, links, location, document, and pictures. This research is aimed at observing WA which is tailored to support English Language Learning (ELL) activities. For gathering data, this study applied case study using observation and questionnaire as main instrument. A case study is drawn from participants of 5th semester students at English Department Universitas Bina Sarana Informatika. It is found that WA was significant in helping ELL activities since it was used by both teachers and students for ELL related activities. The results are: 1) In the field of technical advantages, WA provides simple operation; 2) WA can enhance learning opportunities outside classroom for students. In brief, WA facilitated ELL activities as an effort toward MALL (Mobile-Assisted Language Learning) implementation.